PENGARUH RISIKO KEUANGAN DAN PERTUMBUHAN PENJUALAN TERHADAP PROFITABILITAS (SEBAGAI VARIABLE INTERVENING) DAN NILAI PERUSAHAAN FARMASI PERIODE 2020 -2022 - Dewi, Mariana Puspa; Prasetyo, Irawan Budi (Jurnal Manajemen dan Profesional, 2023)
This study aims to determine the Effect of Financial Risk, Sales Growth on Profitability and Value of Pharmaceutical Companies of pharmaceutical companies in 2020 – 2022. The type of research conducted in this study is quantitative which aims to determine the relationship between independent and bound variables, in this study it is carried out to determine the effect of financial risk, sales growth on profitability as an intervening variable and company value. The source of data used in this study is secondary data in the form of financial statements of pharmaceutical companies listed on the Indonesia Stock Exchange from 2020 to 2022. To determine the effect of DAR and sales growth on profitability and company value using pricebook value, Debt to Asset Ratio, Sales Growth, and Return on Asset ratio. The results showed that DAR had a significant negative effect on profitability. This means that the smaller the DAR value, the greater the level of profitability achieved. Sales growth has no insignificant effect on profitability. That is, the level of sales growth is not the cause of the rise or fall of company profitability. The effect of DAR, Sales Growth and ROA on Company Value. DAR has no effect and is not significant on the Value of the Company. That is, investors look more at the prospects of the company than at the Financial Risk in this case the value of the Debt to Asset Ratio. Sales Growth has a positive and significant effect on Company Value.